Predictors of stillbirths and neonatal deaths in rural western Uganda. Issue 2 (18th April 2016) - Moyer, Cheryl A.; Kolars, Candace K.; Oppong, Samuel A.; Bakari, Ashura; Bell, April; Busingye, Priscilla
Abstract: Objective: To explore pregnancy outcomes at a referral hospital in rural western Uganda. Methods: A retrospective study was undertaken using data for all deliveries at Virika Hospital, Fort Portal, Uganda, between July 1, 2009, and October 22, 2011. A detailed review of delivery logs was conducted. Categories were created for obstetric risk factors (e.g. grand multipara, history of hypertension), maternal delivery complications (e.g. eclampsia, hemorrhage), and neonatal complications (e.g. fetal distress, birth defects). Results: Overall, 4883 deliveries were included. Of the 517 neonates who did not survive, 430 (83.2%) had been stillborn. After controlling for parity, gestational age, obstetric risk factors, and neonatal complications, risk factors for stillbirth included maternal delivery complications (risk ratio [RR] 3.32, 95% confidence interval [CI] 2.34–4.71; P < 0.001) and living 51–100 km from the hospital (RR 3.37, 95% CI 2.41–4.74; P < 0.001). Risk factors for neonatal death included neonatal complications (RR 5.79, 95% CI 2.49–13.46; P = 0.001) and maternal delivery complications (RR 3.17, 95% CI 1.47–6.82; P = 0.003). Conclusion: Qualified providers need to be deployed to rural areas of Uganda to facilitate the prompt identification and management of pregnancy, delivery, and neonatal complications.